CAN TRANSMEDIA STORYTELLING LEARN FROM HYPERTEXT FICTION? INTRODUCING THREE EXAMPLES OF 4TH GENERATION DIGITAL FICTION - Kronman, Linda (AoIR Selected Papers of Internet Research, 2014)
This paper introduces three examples of social media literature, an emerging 4th generation of digital fiction and argues that works that are mostly considered as transmedia storytelling would gain from being viewed from the perspective of hypertext fiction theory. ’The Big Plot’1 (2009), ’Re: Dakar Arts Festival’2 (2011) and ’Grace, Wit & Charm’3(2011) are three examples of digital fiction unfolding on social media networks using microcontent; small chunks of content like blog posts, Youtube videos and Flickr images to assemble their storyworlds. What can we learn about these works if we look at them through the lens of digital fiction focusing on issues of reading it?